IMPLEMENTATION OF BEHAVIOUR BASED NAVIGATION IN A PHYSICALLY CONFINED SITE - ABDUL RAZAK, NUSRAH (2017)
Behaviour-based architecture is one of the most effective autonomous navigation techniques, second only to machine learning. However, specific algorithm may only be effective for a specific environment. When the environment is changed the algorithm may fail to adapt itself to the new configuration. This study looks at developing a behavior-based algorithm that adaptable to several different environment configurations. Selected basic behaviour-based algorithms such as wallfollower, obstacle avoidance, escape route and target detection are to be combined and its efficiency is measured. Experiments conducted in different mazes show that robot is able to navigate itself from the starting point to the target with 4% to 10% extra turns. The efficiency of the mobile robot increases by 77% compared to manually controlled robot. The behaviour based implementation on the mobile robot managed to find the shortest path with the rate of failure of less than 15%. However, the time taken for the robot to reach the target can be variable depending on the complexity of the maze.